Intake and performance of dairy cows fed wet corn gluten feed during the periparturient period - A.F. Park; J.M. Defrain; M. J. Meyer; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2000)
Eight primiparous and nine multiparous Holstein cows were used in a randomized block design to determine the effect of wet corn gluten feed in the diet during the last 21 days of gestation on dry matter intake and early postpartum performance. Multilactation cows fed wet corn gluten feed maintained a higher dry matter intake and intake as a percentage of body weight during the last week before calving than cows fed the control diet. First-lactation cows fed wet corn gluten feed consumed less dry matter, both total and as a percentage of body weight, across calving than first-lactation cows fed the control diet. Milk, milk components, and blood metabolites were not influenced by diet. Wet corn gluten feed may help alleviate the depression in intake typically observed during late gestation for multiparous but not primiparous cows.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Wet corn gluten feed; Transition cow; Intake